Pengurusan Sumber Bekalan Air Bersih : Perbandingan di antara Daerah Klang dengan Daerah Ulu Selangor, Selangor - Selvi, Narayanan (2003)
This is a comparative research on how the state government particularly on the two water supply authorities in the Klang District and Ulu Selangor District manages the water resources supply. The researcher will look into details on how the two authorities manage the water supply through the cooperation of private sector by identifying the management style, problems threats and problem solving alternatives. This is a qualitative research whereby the researcher will not measure the customer satisfaction but will only focus on the water management authority management system. The data collection methods used are face to face interview, library research and through online database. The research will be useful to those who are interested in the field of water resources management and as a guideline for further study. The research offers a few alternatives and measures to be taken in order to ensure a safe efficient supply of water resources as we are enjoying now.